Citrate combustion synthesized Al-doped CaCu3Ti4O12 quadruple perovskite: synthesis, characterization and multifunctional properties. Issue 6 (29th January 2020) - Pal, Kamalesh; Dey, Arka; Jana, Rajkumar; Ray, Partha P.; Bera, Parthasarathi; Kumar, Lalit; Mandal, Tapas Kumar; Mohanty, Paritosh; Seikh, Md. Motin; Gayen, Arup
Abstract : Facile synthesis of Al-doped CaCu3 Ti4 O12 quadruple perovskite has been reported and it is projected to be a promising candidate for Schottky barrier diode application and a methanol steam reforming catalyst for hydrogen generation. Abstract : The facile synthesis of the Al-doped CaCu3 Ti4 O12 quadruple perovskite, a well-known and vastly studied material for various technological applications, using the modified citrate combustion route along with structural, microstructural, and X-ray photoelectron spectroscopic (XPS) characterization and magnetic, dielectric and electrical properties has been investigated and reported here. The possible applications of the material as a Schottky barrier diode (SBD) in optoelectronic devices and as a catalyst in methanol steam reforming (MSR) reaction for hydrogen generation, hitherto unreported in the open literature, have also been explored. The compound is crystallized in the cubic body centered Im 3̄ space group and the particle size is found to be in nanodimension with rather narrow size distribution. The enhanced resistivity could be attributed to the grain boundary effect, and consequently, it exhibits better performance as a SBD compared to the undoped sample. Desired cationic composition with expected valence states within the probe range is confirmed by XPS analysis. A better catalytic activity towards MSR is noticed for the Al-doped CaCu3 Ti4 O12 compared to the undoped composition. These new findings, namely MSR activity and applicability in the Schottky device, have highlighted further the multifunctional nature of the material in energy related issues and would thus be of interest to the materials community searching for functional materials.